(Invited) Interplay between Chemical Composition, Synthetic Parameters and ORR Performance of Pt-Free Electrocatalysts for the ORR Including Graphene-Based Cores and a Carbon Nitride Shell. (19th June 2018) - Negro, Enrico; Nale, Angeloclaudio; Bang, Yannick; Vezzù, Keti; Pagot, Gioele; Rutkowska, Iwona Agnieszka; Kulesza, Pawel J.; Di Noto, Vito
Abstract : This work reports the synthesis of a family of electrocatalysts (ECs) for the oxygen reduction reaction (ORR) that: (i) do not comprise platinum; and (ii) exhibit a "core-shell" morphology. The ECs are based on a "core" of graphene nanoplatelets, that are covered by a carbon nitride (CN) "shell" . The active sites include Fe as the "active metal" and are stabilized in C- and N- "coordination nests" in the CN "shell" . The chemical composition of the proposed ECs is determined by inductively-coupled plasma atomic emission spectroscopy (ICP-AES) and microanalysis; the performance and reaction mechanism in the ORR are elucidated by cyclic voltammetry with the rotating ring-disk electrode (CV-TF-RRDE) technique. This work is a systematic effort aimed at elucidating how (i) the pre-treatment of the graphene "core" ; and (ii) the introduction of Sn as the "co-catalyst" in the active sites influence the chemical composition, the ORR performance and reaction mechanism of the proposed ECs.